The Risk Factors, Complications, Management Strategies and Predictors of Morbidity & Mortality Among Pediatric Patients Presenting with Severe Diarrhea at Muhimbili National Hospital’s Emergency Medicine Department - Manyasani Jisoli Yahula; Hendry Sawe; Said S Kilindimo; Ellen Weber; Juma Mfinanga; Catherine Shari; Masuma A. Gulamhussein; Winnie Mdundo (Journal of Current Scientific Research, 2026)
Background Acute diarrhea is the major cause of health public problem among paediatric patients in Tanzania. And in Low income countries (LICs), studies have shown, Acute watery Diarrhea (AWD) is the cause of morbidity and mortality which can be prevented by immediate identification and treatment of complications. Methods A prospective cohort study was done between December 2021 and April 2022 to determine the risks, complications, management strategies and predictors of mortality among paediatric patients ≤12 years of age with severe diarrhea. We excluded those who arrived in cardiac arrest at the Emergency Medicine Department (EMD) of Muhimbili National Hospital (MNH). Proportion was used to summarize the counts and frequency of participants who were at risk of complications and management strategies given and for predictors of outcomes. A Modified Poisson log linear model with a robust estimation test was used to test for significant associations between predictors and outcomes. Multivariate logistic regression was used to adjust for confounders. Results A total 6,570 paediatric patients presented to EMD during study period, and we recruited 144 (2.2%). The median age was 1 (IQR 0.7-2.0) years and most were male 86 (59.7%). Among the study participants with diarrhea, 120 (83.3%) had dehydration, acidosis 60 (42.3%), hypoglycemia 8 (5.6%), hypokalemia 76 (53.1%), and Acute renal failure 11 (7.6%). Those patients with complications received appropriate management, including IV crystalloid solution given to 131 (90.97%), and correction of acidosis 60 (42.3%), hypoglycemia correction with IV dextrose 10% 6 (4.2%), and hypokalemia and infections were corrected with IV potassium chloride 52 (36.1%) and IV antibiotic treatment 84 (58.3%) respectively. Conclusion Pediatric patients under 2 years of age are at high risk of severe diarrhea with dehydration as compared to other ages. Early referral and availability of point care tests are essential in early recognition of accompanied complications.
Keywords: Severe diarrhea